Relativistic and resonant effects in the ionization of heavy atoms by ultra-intense hard X-rays - Rudek, Benedikt; Toyota, Koudai; Foucar, Lutz; Erk, Benjamin; Boll, Rebecca; Bomme, Cédric; Correa, Jonathan; Carron, Sebastian; Boutet, Sébastien; Williams, Garth J.; Ferguson, Ken R.; Alonso-Mori, Roberto; et al. (My University, 2018)
Availability of intense hard X-ray pulses allows exploration of multiple ionization effects in heavier elements. Here, the authors measure the complex charge state distributions of xenon and found a reasonable agreement by comparing with the model including the relativistic and resonance effects.
Citation: Rudek, B., Toyota, K., Foucar, L., Erk, B., Boll, R., Bomme, C., … Rolles, D. (2018). Relativistic and resonant effects in the ionization of heavy atoms by ultra-intense hard X-rays. Nature Communications, 9(1), 4200. https://doi.org/10.1038/s41467-018-06745-6
Keywords: Atomic and molecular interactions with photons; Electronic structure of atoms and molecules; Free-electron lasers